Absolute risk of tuberculosis among untreated populations with a positive tuberculin skin test or interferon-gamma release assay result: systematic review and meta-analysis. (10th March 2020) - Campbell, Jonathon R; Winters, Nicholas; Menzies, Dick
Abstract: Objective: To determine the annual rate of tuberculosis development after a positive tuberculin skin test (TST) or interferon-gamma release assay result (IGRA), or both, among untreated populations with characteristics believed to increase the risk of tuberculosis (at risk populations). Design: Systematic review and meta-analysis. Data sources: Embase, Medline, and Cochrane Controlled Register of Trials from 1 January 1990 to 17 May 2019, for studies in humans published in English or French. Reference lists were reviewed. Eligibility criteria and data analysis: Retrospective or prospective cohorts and randomised trials that included at least 10 untreated participants who tested positive to tuberculosis antigens (contained in TST or IGRA, or both) followed for at least 12 months. Following the preferred reporting items for systematic reviews and meta-analyses (PRISMA) and meta-analyses of observational studies in epidemiology (MOOSE) guidelines, two reviewers independently extracted study data and assessed quality using a modified quality assessment of diagnostic accuracy studies (QUADAS-2) tool. Data were pooled using random effects generalised linear mixed models. Main outcome measures: The primary outcome was tuberculosis incidence per 1000 person years among untreated participants who tested positive (TST or IGRA, or both) in different at risk subgroups. Secondary outcomes were the cumulative incidence of tuberculosis and incidence rate ratios among participants with a positive test result for latent tuberculosis infection compared with those with a negative test result in at risk subgroups. Results: 122 of 5166 identified studies were included. In three general population studies, the incidence of tuberculosis among 33 811 participants with a TST induration of ≥10 mm was 0.3 (95% confidence interval 0.1 to 1.1) per 1000 person years. Among 116 197 positive test results for latent tuberculosis infection in 19 different at risk populations, incidence rates were consistently higher than those in the general population. Among all types of tuberculosis contacts, the incidence of tuberculosis was 17.0 (95% confidence interval 12.9 to 22.4) per 1000 person years for participants with a positive IGRA result and 8.4 (5.6 to 12.6) per 1000 person years for participants with a positive TST result of ≥5 mm. Among people living with HIV, the incidence of tuberculosis was 16.9 (10.5 to 27.3) for participants with a positive IGRA result and 27.1 (15.0 to 49.0) for participants with a positive TST result of ≥5 mm. Rates were also high for immigrants, people with silicosis or requiring dialysis, transplant recipients, and prisoners. Incidence rate ratios among test positive versus test negative participants were significantly greater than 1.0 in almost all risk groups, for all tests. Conclusions: The incidence of tuberculosis is substantial in numerous at risk populations after a positive TST or IGRA result. The information from this review should help inform clinical decisions to test and treat for latent tuberculosis infection. Study registration: PROSPERO CRD42019136608.